Relasi Agama, Kebudayaan dan Politik Pada Masyarakat Batak Toba di Kabupaten Samosir - Harisan Boni Firmando; Elvri Teresia Simbolon; Roida Lumbantobing (Jurnal Sosiologi Agama Indonesia, 2023)
Religion, culture, and politics are one unit in society that cannot be separated. These three things cause human life as a social being and as a citizen to take place. The purpose of this study was to determine the relationship between religion, culture and politics in the Toba Batak community in Samosir Regency. This research was conducted using qualitative research methods to understand the phenomenon of what was experienced by the research subjects as a whole. The results of the study show that the relationship between religion, culture and politics can be seen in the implementation of the dalihan na tolu kinship system. The Toba Batak community with other people outside the Toba Batak tribe; this openness is carried out by adding the clan as the basis for the Toba Batak tribe to determine the kinship system. The culture of solidarity guides the Batak Toba community in behaving politically. The community will help their families who run in general elections. This solidarity is social capital as well as economic capital for the Toba Batak people who carry out political activities, especially members of the community who are advancing to become candidates for regional heads and members of the council. The selection of leaders in the Batak Toba community is still taking into account the background of a candidate. The background is not only from education or other capital from qualified prospective leaders but rather from sociological aspects.